Teacher education for their narratives: the challenges of teaching - Ferreira, Luciana Haddad; Prado, Guilherme do Val Toledo; Aragão, Ana Maria Falcão de (Revista Hipótese, 2015)
Whereas one of the challenges of education today is the relationship between doing and thinking teaching, we , the research presented , the narrative as constitutive of teacher training. The analyzes point to the continuing education that values knowledge and considers perception and aesthetic exercise into / from school everyday. Finally , we point dimensions of narrative writing that are articulated with teaching lead the teacher to see how the very formation agent.
Keywords: Narrative; Teacher training; Aesthetic Education; Everyday